Evaluating the Disparate Use of Knee Arthroplasty Among Minorities Using Social Vulnerability Index - Manasa Pagadala, BA; Rachel Bergman, MD; T. Jacob Selph, Jr., BS; Patricia Franklin, MD, MPH, MBA; Adam I. Edelstein, MD; Linda I. Suleiman, MD (Arthroplasty Today)
Background: Total knee arthroplasty (TKA) is an effective treatment for advanced osteoarthritis, but disparities in its utilization exist, particularly by gender, race, socioeconomic status, and geography. Social determinants of health may contribute to these disparities. This study examines the relationship among the Social Vulnerability Index (SVI), a measure of social determinants of health, and the likelihood of receiving a surgeon's recommendation for TKA. Methods: This prospective, observational study included 314 patients with primary knee osteoarthritis deemed “appropriate” for TKA based on the American Academy of Orthopaedic Surgeons Appropriate Use Criteria. Patients were recruited from 4 fellowship-trained arthroplasty surgeons at a single academic hospital in Chicago. The primary outcome was whether patients received a surgeon recommendation for TKA, analyzed in relation to their SVI. Bivariate and multivariable analyses were performed, adjusting for patient demographics, body mass index, Charlson Comorbidity Index, and surgeon factors. Results: Of the 314 patients appropriate for TKA by Appropriate Use Criteria guidelines, 39.2% received a surgeon recommendation. Patients with lower SVI scores were more likely to receive a recommendation (0.6596 vs 0.7556, P = .284). Multivariable analysis showed that lower SVI scores were independently associated with higher odds of a surgeon recommendation (odds ratio [OR]: 0.705, P = .028), particularly in the subcategories of socioeconomic status (OR: 0.754, P = .034) and household characteristics (OR: 0.803, P = .049). Conclusions: Lower SVI scores are associated with increased likelihood of receiving a TKA recommendation, highlighting the impact of social vulnerability on clinical decision-making and the need for further investigation into mitigating biases in surgical decisions.